ҚАРАҚАЛПАҚ ШАҢАРАҚЛАРЫНДА НЕКЕ АЛДЫ ФАКТОРЛАРЫНЫҢ ЭТНОПСИХОЛОГИЯЛЫҚ ӨЗГЕШЕЛИКЛЕРИ - Утепбергенов, М.А. (SCIENCE and SOCIETY, 2016)
The article deals with ethno-psychological peculiarities of pre-marriage factors of Karakalpak family in comparison with other nationalities. The author of the article studies the issues of influence of pre-marriage factors on the future family, importance of such types of marriage as ekzogam and endogam. There have been analyzed the age, motives and period of tet-a-tet before the marriage.